THE IMPACT OF PATRIOTISM AND RELIGIOSITY ON TAX EVASION: DOES TAX MORALE MEDIATE? - Girindratama, Muhammad Wisnu; Ach Maulidi; Alnajar, Ali Elazumi Ali (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
This study investigates the influence of patriotism and religiosity on tax evasion, with tax morale as a potential mediator. The research is motivated by the need to understand behavioural and ethical factors that drive taxpayers’ compliance beyond deterrence measures. Data were collected from business students via a questionnaire and analysed using partial least squares structural equation modelling (PLS-SEM). The results indicate that patriotism and religiosity do not directly reduce tax evasion intentions. Instead, both positively affect tax morale, which, in turn, significantly reduces the likelihood of tax evasion. Moreover, tax morale mediates the effect of patriotism on tax evasion but does not mediate the effect of religiosity. These findings provide theoretical insights into the role of ethics in tax compliance and offer practical recommendations for tax authorities to strengthen compliance by fostering tax morale.